The Causation Paradox: Who Bears the Cost in a Sea of Liable Parties? - Maldonado Garcés, Nicolás Camilo (2025)
Causation is a necessary link between an unlawful act and the damage, determining who must assume the obligation to compensate for an injury caused. Tort law faces significant challenges in complex cases involvingmultiple actors and various causalities contributing to the damage. In light of these situations, causation currents have developed different tools that allow the identification of responsible parties, even attributing liability to more than one individual, provided that their actions meet the criteria of legal relevance and causal proximity. Despite these advances, a notable regulatory gap exists in tort and civil liability. There is no clarity in the legal framework that contemplates solidarity among liable parties in cases where independent unlawful acts concur to cause damage. Ideally, this concurrence should give rise to a regime of solidarity among tortfeasors, allowing compensation burdens to be assigned equitably. However, due to the limitations inherent in the traditional sources of solidarity, such a regime is not feasible. In these cases, the absence of a mechanism to establish a right of recourse underlines the need for legislative reform. A normative development regulating proportional solidarity in cases of concurrence of wrongful acts would be essential to ensure a fair redistribution of compensation burdens.